2008
DOI: 10.1146/annurev.arplant.59.032607.092949
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Regulatory Network in the Development of Trichomes and Root Hairs

Abstract: Trichomes and root hairs differentiate from epidermal cells in the aerial tissues and roots, respectively. Because trichomes and root hairs are easily accessible, particularly in the model plant Arabidopsis, their development has become a well-studied model of cell differentiation and growth. Molecular genetic analyses using Arabidopsis mutants have demonstrated that the differentiation of trichomes and root hair/hairless cells is regulated by similar molecular mechanisms. Transcriptional complexes regulate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
467
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(487 citation statements)
references
References 143 publications
8
467
1
6
Order By: Relevance
“…When 10 µM GA 3 was applied, the transcript levels of GL1, TTG1, and SPY significantly increased or decreased, in a tendency opposite to that in dxr mutant (Figure 7). This result is consistent with the important role of GAs in trichome formation and development [43][44][45].…”
Section: Dxr Transcript Level Affects the Transcription Of Many Genessupporting
confidence: 90%
See 1 more Smart Citation
“…When 10 µM GA 3 was applied, the transcript levels of GL1, TTG1, and SPY significantly increased or decreased, in a tendency opposite to that in dxr mutant (Figure 7). This result is consistent with the important role of GAs in trichome formation and development [43][44][45].…”
Section: Dxr Transcript Level Affects the Transcription Of Many Genessupporting
confidence: 90%
“…In addition to the albino phenotype, we also found trichome initiation and stomata closure defects as a result of DXR disruption. It was previously reported that GAs play important roles in trichome development by regulating trichome-associated genes including GL1, GL3, and SPY [41][42][43][44][45]. As GAs are a class of important products derived from MEP-related isoprenoid biosynthetic pathways, it is reasonable to link DXR disruption to the observed trichome developmental defects.…”
Section: Discussionmentioning
confidence: 99%
“…Root hairs are tubular outgrowths of epidermis cells. They absorb water and nutrients, interact with microorganisms, and anchor the plant to the soil (Ishida et al, 2008). Using Arabidopsis (Arabidopsis thaliana) as a model, the genetics and molecular mechanisms of root hair formation have been studied extensively.…”
mentioning
confidence: 99%
“…The root hairs develop in the differentiation zone of the root (Petricka et al, 2012). In Arabidopsis, the root epidermis layer consists of nonhair and hair cells, and their differentiation is tightly controlled by defined transcriptional complexes (Ishida et al, 2008). The polar growth of root hairs involves Ca 2+ and ROS signals, which are required for the maintenance of cell wall integrity at the tip of growing root hairs (Datta et al, 2011).…”
mentioning
confidence: 99%
“…1,4,9,11,25 The TTG1-GL3/ EGL3-WER transcriptional complex promotes GL2 expression to induce a hairless cell differentiation. 26,27 CPC disrupts this transcriptional complex by competing with WER, thus negatively regulating the expression of GL2 and resulting in root hair formation. 28 In addition to the root hair formation in the major portion of the root, CPC family genes are also involved in root hair formation at the root-hypocotyl junction.…”
mentioning
confidence: 99%